If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 2xy + -6 = 0 Reorder the terms: -6 + 2x + 2xy = 0 Solving -6 + 2x + 2xy = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 2x + 6 + 2xy = 0 + 6 Reorder the terms: -6 + 6 + 2x + 2xy = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 2x + 2xy = 0 + 6 2x + 2xy = 0 + 6 Combine like terms: 0 + 6 = 6 2x + 2xy = 6 Reorder the terms: -6 + 2x + 2xy = 6 + -6 Combine like terms: 6 + -6 = 0 -6 + 2x + 2xy = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-3 + x + xy) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-3 + x + xy)' equal to zero and attempt to solve: Simplifying -3 + x + xy = 0 Solving -3 + x + xy = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + x + 3 + xy = 0 + 3 Reorder the terms: -3 + 3 + x + xy = 0 + 3 Combine like terms: -3 + 3 = 0 0 + x + xy = 0 + 3 x + xy = 0 + 3 Combine like terms: 0 + 3 = 3 x + xy = 3 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 3x-3x=-3 | | -3y-7=-10y+21 | | 400=1.5x | | 144x^2-121y^2=0 | | 4x^2=-2x | | -8(-8m-6)=-6m-22 | | 4v-2=-10 | | 1920*x=195 | | 18(1-a)= | | 134=14c | | 2(q+2)=8 | | 3/4=Y/7 | | 1080*x=917 | | 1080-x=163 | | -24=-12w | | -7=3v+2 | | 24=-w/6 | | 4z/7-5=-2 | | 144+12c=300 | | 2*2*2+-3*-3= | | 1080*x=955 | | -u/6=-42 | | 20=2+3u | | (7x^4)/(sqrt(2x-8)) | | 2.3log(x)=3log(6-x) | | 6x+y+z=10 | | -4u+5=5-4u | | 1920*x=5 | | -15=4u-3 | | 4lnx-1=6 | | 5/4=7x^2-x | | 42+x=(13+x)*2 |